2013
DOI: 10.1121/1.4812863
|View full text |Cite
|
Sign up to set email alerts
|

Computation of nonlinear ultrasound fields using a linearized contrast source method

Abstract: Nonlinear ultrasound is important in medical diagnostics because imaging of the higher harmonics improves resolution and reduces scattering artifacts. Second harmonic imaging is currently standard, and higher harmonic imaging is under investigation. The efficient development of novel imaging modalities and equipment requires accurate simulations of nonlinear wave fields in large volumes of realistic (lossy, inhomogeneous) media. The Iterative Nonlinear Contrast Source (INCS) method has been developed to deal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…( 29) is related to the wave equation ( 1) in Verweij et al (2013) (see also the references therein). These two wave equations are mathematically similar if nonlinear terms are disregarded, and if m(t) in Verweij et al (2013) is identified as m(t) = ρ 0 c 2 0 κ(t). Related similarity is observed between Eq.…”
Section: Convolution Formulation Of the Multiple Relaxation Modelmentioning
confidence: 99%
“…( 29) is related to the wave equation ( 1) in Verweij et al (2013) (see also the references therein). These two wave equations are mathematically similar if nonlinear terms are disregarded, and if m(t) in Verweij et al (2013) is identified as m(t) = ρ 0 c 2 0 κ(t). Related similarity is observed between Eq.…”
Section: Convolution Formulation Of the Multiple Relaxation Modelmentioning
confidence: 99%
“…These numerical methods can be used for all complex interfaces and for anisotropic materials, but they become computationally very expensive, especially in the case where 3-D models are required. Some other methods for beam modeling, such as applying the full-wave methods by Green's solution to the dispersive wave equation [11], using nonlinear acoustics [12]- [17], etc., have been explored for isotropic homogeneous and inhomogeneous media, but have yet to be applied to layered anisotropic media. An alternative method which is based on paraxial approximation is to model the radiation as a superposition of Gaussian beams.…”
Section: Simulation Of Ultrasonic Beam Propagation From Phased Arrays In Anisotropic Media Usingmentioning
confidence: 99%
“…It has been formulated in its original form by Huijssen (2008) and Huijssen and Verweij (2010), and later, extensions have been described by Demi et al (2011), Demi (2013, and Verweij et al (2013). The method is based on the IE for a nonlinear contrast source problem.…”
Section: Texas Codementioning
confidence: 99%